Incidence and Diagnosis of Ampullary Carcinoma in Dhulikhel Hospital, Kathmandu University Hospital - Dhakal, B.; Makaju, R. (Kathmandu University Medical Journal, 2021)
Background Endoscopy from a suspected ampulla of vator may establish an early preoperative diagnosis of ampullary carcinoma. However, information regarding the diagnostic accuracy of this procedure is limited and variable. Objective To study the preoperative diagnostic accuracy of Endoscopic/ERCP appearance of ampullary tumors with that of endoscopic biopsy. Method Among patients who were performed endoscopy during a one year period; a suspicious ampulla of vator was seen in 44 cases. Endoscopic biopsy specimens were classified into four groups based on the degree of epithelial atypia: group 1 (no evidence of malignancy), group 2 (presence of dysplasia), group 3 (suspicious of malignancy) and group 4 (positive for malignancy). In each case comparison was made between the pre-endoscopic biopsy clinical diagnosis and endoscopic appearance. Result Endoscopic biopsy diagnosis of malignancy (group 4) were seen in 22 cases, Suspicious of malignancy (group 3) in 3 cases, dysplasia (group 2) in 9 cases and no evidence of malignancy (group 1) in 10 cases. Pre-endoscopic diagnostic accuracy of endoscopy/ ERCP was 50% compared to the diagnosis by biopsy. Conclusion Diagnostic accuracy of endoscopy/ERCP was 50% compared to the diagnosis by biopsy. A diagnosis of non malignancy in the forceps biopsy material does not rule out the presence of cancerous foci in ampullary neoplasms.